شرعية تعديل العقوبات السالبة للحرية المحكوم بها: أسلوب حديث لتعزيز أنسنة العقوبة - الكاهية، سعيد Alkahiah, Said (صلاح الدين دكداك, 2022)
تعرف مرحلة التفريد التنفيذي للعقوبة السالبة للحرية العديد من المحطات في مسلسل تنزيل العقوبات المحكوم بها، إذ يمكن أن تشهد هذه الأخيرة العديد من المتغيرات في الكم وفي النوع، وذلك فيما يعرف بتعديل العقوبات وتغييرها من أجل إحقاق أهداف هذه العقوبة وأنسنتها، وأيضا من أجل دعم المؤسسات العقابية في مهامها الإصلاحية والتربوية. ويعتبر موضوع التخفيض من مدة العقوبة السالبة للحرية المحكوم بها، وأيضا الرخص الاستثنائية للخروج من السجن، سواء في إطار الرخص البسيطة للخروج، أو في إطار نظام العمل العقابي خارج أسوار المؤسسة السجنية؛ تعتبر من أهم الأساليب العقابية التي تروم درء مفاسد الاعتقال خاصة في قضايا الجرائم البسيطة، مما يساهم أيضا في التخفيف من أعداد الساكنة السجنية، وفتح المجال أمام المفرج عنهم قصد الإدماج مرة أخرى داخل المجتمع. The stage of executive individualization of custodial sentences defines many stations in the process of executing the sentences pronounced. The latter can testify to many variables in quantity and type, in what is called the adjustment of sentences, In order to achieve the objectives of this sentence and its humanization, but also to support penitentiary establishments in their correctional and educational missions. The subject of the reduction in the length of the custodial sentence imposed, as well as exceptional authorizations to leave prison, whether within the framework of simple exit authorizations, or within the framework of the regime of punitive work outside the walls of the penitentiary establishment, It is considered one of the most important punitive methods aimed at warding off the evils of detention, Especially in petty crime cases, This also contributes to reducing the prison population, and paving the way for released prisoners to reintegrate into society.
Keywords: التفريد العقابي -- النظام العقابي -- الأحكام القضائية